Kebijakan Manajemen Leverage dan Pengaruhnya Terhadap KEnaikan Profitabilitad Perusahaan Studi Kasus pada Perusahaan PT Charoen Pokphan Indonesia, Tbk - Santoso, Hadi (MABIS, 2011)
The use of leverage in running a company aims to increase its profit. Leverage can be differentiated into two; operating and financial leverage. In the daily operations, the company uses both leverages simultaneously. In other words, the company uses a combined leverage. The aim is to increase the shareholders net income or earnings per share because of the increase in the sales resulted from the use of leverage. This study aims to determine the extent of the influence of using combined leverage to increase return on equity and earnings per share. The study was conducted using case study method. The poultry feed company, PT Charoen Pokphan Indonesia, Tbk (CPIN), became the object of the research. The results show that CPIN used a fairly large leverage in its operation during 2005 to 2008. However, the company management took another policy which was to reduce the use of operational leverage in 2009. The result indicates that the use of leverage did not bring significant impact on improving ROE and EPS. This happened because the cost of the companys operations outside the fixed costs as a result of using leverage was very large. Therefore, CIPN should control its operational costs in the future.